2012
DOI: 10.1042/bj20120257
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhibits the ATPase activity of the chaperone-like AAA+ ATPase CDC48, a target for S-nitrosylation in cryptogein signalling in tobacco cells

Abstract: NO has important physiological functions in plants, including the adaptative response to pathogen attack. We previously demonstrated that cryptogein, an elicitor of defence reaction produced by the oomycete Phytophthora cryptogea, triggers NO synthesis in tobacco. To decipher the role of NO in tobacco cells elicited by cryptogein, in the present study we performed a proteomic approach in order to identify proteins undergoing S-nitrosylation. We provided evidence that cryptogein induced the S-nitrosylation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 54 publications
1
50
0
1
Order By: Relevance
“…Further, several studies suggest an active role of mitochondria in plant responses to fungi, such as the early generation of mitochondrial ROS shown to precede a fungal elicitor-induced HR [230] or a fungal toxin-induced cell death [231]. Fungal infection is also associated with generation of NO and CN, that could potentially perturb mitochondrial function [232,233]. However, relatively little work has been reported to establish whether AOX has a critical role in plant responses to pathogenic fungi.…”
Section: Alternative Oxidase During Abiotic and Biotic Stressmentioning
confidence: 99%
“…Further, several studies suggest an active role of mitochondria in plant responses to fungi, such as the early generation of mitochondrial ROS shown to precede a fungal elicitor-induced HR [230] or a fungal toxin-induced cell death [231]. Fungal infection is also associated with generation of NO and CN, that could potentially perturb mitochondrial function [232,233]. However, relatively little work has been reported to establish whether AOX has a critical role in plant responses to pathogenic fungi.…”
Section: Alternative Oxidase During Abiotic and Biotic Stressmentioning
confidence: 99%
“…In this study S-nitrosylation of the chaperonlike AAA+ ATPase cell division cycle 48 (CDC48) protein has been characterized. The authors demonstrated that Cys110, Cys526 and Cys664 are S-nitrosylated and that NO abolished ATPase activity of this protein [63]. We identified Arabidopsis CDC48 as candidate protein for S-nitrosylation in the nuclear fraction of Pst avr treated cells suggesting a common function of this protein in a biotic stress response in plants.…”
Section: Discussionmentioning
confidence: 95%
“…These include structural, signalling pathogen-and stress related proteins as well as enzymes involved in carbon and nitrogen mobilization and antioxidant defense reactions. Moreover, 11 candidates were identified in tobacco cell suspensions treated with cryptogein, which were involved in amino acid biosynthetic pathways, energy and metabolism, signalling, and protein degradation [63]. In this study S-nitrosylation of the chaperonlike AAA+ ATPase cell division cycle 48 (CDC48) protein has been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, NO-mediated modification of protein activity was found in the enzymes associated with the ROS production such as NADPH oxidases (inactivation through the reversible S-nitrosylation of the putative conserved specific cysteine residue at the C-terminal region, a region with FAD binding site) (Yun et al, 2011), and also with the enzymes involved in scavenging of cellular ROS such as catalases (Clark et al, 2000), ascorbate peroxidases (Clark et al, 2000;de Pinto et al, 2013) and monodehydroascorbate reductases (Begara-Morales et al, 2014). However, none of the antioxidant enzymes were found to be S-nitrosylated in cryptogein-treated tobacco cells (Astier et al, 2012) which could minimize although not completely exclude the occurrence of these processes. Nevertheless, NO can react with superoxide anion as well leading to the generation of peroxynitrite (ONOO À ), a molecule causing nitration of protein tyrosine residues .…”
Section: The Effect Of Cryptogein Protein Variants On the Early Phasementioning
confidence: 93%